Antibody–drug conjugates in colorectal cancer: advances in targeted delivery and personalized oncology - Wang, Huanle; Yan, Xueyan; Xia, Cong; Chen, Danni; Pan, Bo; Zhang, Yinan; Zhang, Qianshi (Frontiers in Bioengineering and Biotechnology, 2026)
Colorectal cancer remains among the most prevalent gastrointestinal malignancies worldwide, imposing a substantial clinical burden and highlighting the urgent need for precision and personalized treatment strategies. Conventional drug delivery approaches are limited by low selectivity, restricted bioavailability, and systemic toxicity, thereby limiting therapeutic efficacy. Antibody–drug conjugates, as advanced delivery plat-forms, have the advantages of highly specific antibody recognition, versatile cytotoxic payloads, and continuously evolving linker technologies. This combination provides novel opportunities to increase efficacy, reduce toxicity, and enable individualized precision therapy. Recent advances have demonstrated the potential of ADCs in CRC, yet challenges such as resistance, toxicity, and clinical translation persist. Multidisciplinary efforts among the pharmaceutical industry and molecular biology and clinical medicine fields will be essential to accelerate the development of more precise and personalized CRC therapies. This review summarizes the current research progress on ADCs as a treatment option for CRC, discusses innovations in delivery system design, examines the key challenges of personalization, and highlights future directions to better integrate ADCs into effective treatment paradigms.